Motivations for Using Electronic Cigarettes in Young Adults: A Systematic Review. Issue 3 (July 2020) - Kinouani, Shérazade; Leflot, Chloé; Vanderkam, Paul; Auriacombe, Marc; Langlois, Emmanuel; Tzourio, Christophe
Background: The most common reasons why adults use e-cigarettes are to stop or reduce tobacco smoking. However, it is unclear if this reason is evenly distributed between young and older adults. Objectives: describe the motivations for e-cigarette use amongst young adults aged 18–25 and compare the reasons for using e-cigarettes of people who currently or formerly used tobacco products to those who had never smoked tobacco prior e-cigarette use. Methods: PubMed ®, Scopus ®, Cochrane Library ®, SocINDEX ®, PsycARTICLES ®, Psychology and Behavioral Sciences Collection ® and PsycINFO ® databases were used. English written articles were screened up to March 2018. Depending on study design, quality was assessed using The STROBE or RATS checklists. Results: Six articles were included in the review, all with a moderate quality of evidence. Independently of smoking status, curiosity was the most frequently reported reason for initiating the use of e-cigarettes in young adults. Reasons for continuing to use e-cigarettes were various. The continued use of e-cigarettes could be either a means to replicate smoking habits, or a way for a different and personalized use of nicotine by inhalation. Conclusions: Reasons for using e-cigarettes in young adults are varied and are not limited to stopping smoking.